1995
DOI: 10.1021/ja00107a010
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics and Photochemistry of Intramolecular Stilbene-Amine Exciplexes

Abstract: The photophysical and photochemical behavior of a series of trans-(aminoalky1)stilbenes in which a primary, secondary, or tertiary amine is appended to the stilbene ortho position with a methyl, ethyl, or propyl linker has been investigated. The tertiary (aminoalky1)stilbenes form fluorescent exciplexes and undergo trans-cis isomerization, but fail to undergo intramolecular reactions analogous to intermolecular addition reactions observed for stilbene with tertiary amines. The photophysical behavior of the ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The photoreactions of trans-stilbene with tertiary aliphatic amines in solvents of various polarity have been intensively investigated. [1][2][3][4][5] Most effort has been put into the time-resolved studies, including a Hammett correlation for various p-conjugating substituents R in Me 2 NCH 2 R 3 and the direct observation of N,N-diethylvinylamine formed from triethylamine (TEA) by chemically induced dynamic nuclear polarization. 4 The photoproducts of trans-stilbenes generally result from amine and=or H-atom addition to the central double bond.…”
Section: Introductionmentioning
confidence: 99%
“…The photoreactions of trans-stilbene with tertiary aliphatic amines in solvents of various polarity have been intensively investigated. [1][2][3][4][5] Most effort has been put into the time-resolved studies, including a Hammett correlation for various p-conjugating substituents R in Me 2 NCH 2 R 3 and the direct observation of N,N-diethylvinylamine formed from triethylamine (TEA) by chemically induced dynamic nuclear polarization. 4 The photoproducts of trans-stilbenes generally result from amine and=or H-atom addition to the central double bond.…”
Section: Introductionmentioning
confidence: 99%
“…This should provide the existence of a suitably high density of fluorophore molecules, which allow the interaction of singlet trans-stilbene with different amines for the observation of appreciable fluorescence quenching. It should be noted that an electron transfer between the electron donor (ground-state amine) and the acceptor molecules (singlet trans-stilbene) lead either to an exciplex or an ion pair of stilbene radical anions type and amine radical cations within a solvent cage [27]. Figure 4a shows the plot of the fluorescence emission spectra for poly(AcPheBzco-DMAQ) in DMF solution, excited at 334 nm and recorded in the presence and absence of monomethyl viologene as electron donor.…”
Section: Resultsmentioning
confidence: 99%
“…One mechanism for the red‐shifted fluorescence emission and lengthened fluorescence lifetime at higher temperature is the formation of an exciplex, and these authors suggested two complementary scenarios by which this could occur 1. One involved the intimate interaction between a nearby tryptophan (Trp‐A106)and characterized by significant sharing of charge distribution between stilbene and the tryptophan side chain 19. Another posited that subtle changes in the vibronic coupling between the protein environment and the ligand could lead to the observed lifetime increase of the fluorescence emission with temperature 1.…”
Section: Introductionmentioning
confidence: 99%